Does 'fear of dying' indicate a more severe presentation of panic disorder?. (May 2016) - Gazarian, Douglas; Multach, Matthew D.; Ellison, William D.; Chelminski, Iwona; Dalrymple, Kristy; Zimmerman, Mark
Highlights: The clinical significance of 'fear of dying (FOD) in panic disorder (PD) is explored. PD patients reporting FOD had more symptomatic panic attacks and agoraphobia. Differences in clinical impairment as a function of FOD were not found. FOD may be a meaningful indicator for significant psychiatric distress in PD, but not necessarily impairment. Abstract: Research suggests a relationship between the presence of fearful cognitions and panic disorder (PD) severity. With little existing evidence addressing the clinical significance of individual panic-cognitions, the current study examined presentation and impairment differences among 331 outpatients with PD according to whether they experience "fear of dying" (FOD) during panic attacks. Patients reporting FOD (n = 153) were compared to patients denying FOD (n = 178) on variables indicating PD severity (e.g., number of symptoms) and psychiatric impairment (e.g., hospitalizations). PD patients with FOD reported a greater number of panic symptoms, agoraphobia diagnoses, and were more likely to be seeking treatment primarily for PD. We found no clinical impairment or comorbidity differences between groups. Results suggest that panic attacks with FOD are related to a more acute presentation of PD. Such results substantiate past research connecting cognitive distress and PD severity and further suggest that FOD may be particularly relevant to this relationship.